Pengaruh Pendidikan Agama Islam dan Budaya Religius Sekolah Terhadap Kecerdasan Emosional dan Spiritual Siswa - Firdausi, Zakaria (Jurnal al Hikmah, 2017)
Many people who think that to achieve high learning achievement required high intellectual intelligence (IQ). However, according to the results of psychological research proves that IQ is not the only factor that affects a persons learning achievement, but there is another factor, namely emotional intelligence (EQ). a child who has this emotional intelligence, he can recognize the emotions themselves, manage the emotions themselves, recognize the emotions of others, and can work with others. After further research, it turns out that emotional intelligence is not the determinant of ones intellectual intelligence, there is still a higher one, the spiritual intelligence (SQ). With this spiritual intelligence the emotional and intellectual intelligence will run effectively.